An Experimental Test of the Interaction of the Insurance and Information‐Signaling Hypotheses in Auditing* - O'Reilly, Dennis M.; Leitch, Robert A.; Tuttle, Brad (Contemporary Accounting Research, 2006)
Abstract Three incentives for hiring auditing services have been proposed in the literature: (1) to signal outsiders about the company's prospects, (2) to provide a potential source of loss recovery for investors (insurance), and (3) to reduce agency costs. The objective of this study is to examine the potential for the first two (signaling and insurance) to interact while controlling for agency costs. We conduct an experiment in which highly experienced financial analysts provide stock price estimates for a company that is under financial stress. We manipulate, between participants, the signal provided by the audit opinion (going‐concern modification, yes/no) and the ability of investors to recover losses from auditors. The key finding is that the effect of the going‐concern opinion on investor value judgements is moderated by the extent to which the auditor provides an insurance function. Specifically, the negative effect of a going‐concern opinion on the analysts' stock price estimates is reduced by the extent that the environment treats the auditor as an insurer.